Pengertian Dasar- Dasar dan Ruang Lingkup Bahasan Peradaban Islam - Husnayayin, Atina; Sulistri, Sulistri; Sulhani, Sulhani; Malasari, Junita (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The research that will be conducted aims to provide an understanding related to the history of Islamic civilization and how to research using a literature study (library study) sources come from journals, books, articles related to the theme to be discussed. Data obtained from previous research as a reference in completing this research. For the stages of producing this information, there are several stages, namely identifying problems, obtaining correct information, analyzing the findings obtained and developing with new findings related to the history of Islamic civilization and historical study methods. This civilization is used as evidence that there is cultural development from generation to generation in the future. Islam itself is a perfect religion from Allah SWT to all humans through messengers. Civilization is used as evidence in providing cultural development in every era. Islam is a religion that comes from Allah SWT revealed to the prophet Muhammad for his people. Islamic teachings are taught in the Qur'an as a book for Muslims used as a guide for mankind. Then it comes from the hadith which contains events during the time of the prophet. Both are used as a guide for Muslims so that every human behavior must be in accordance with Islamic teachings contained in the Quran and Hadith. With the presence of Islam brings changes to become an advanced and civilized nation. The increasingly rapid development so that it can provide guidance in culture and civilization has an important role in the history of the presence of humans in every era.